An emerging treatment option for glaucoma: Rho kinase inhibitors - Wang, Sean K (Dove Medical Press, 2014)
Rho kinase (ROCK) inhibitors are a novel potential class of glaucoma therapeutics with multiple compounds currently in Phase II and III US Food and Drug Administration trials in the United States. These selective agents work by relaxing the trabecular meshwork through inhibition of the actin cytoskeleton contractile tone of smooth muscle. This results in increased aqueous outflow directly through the trabecular meshwork, achieving lower intraocular pressures in a range similar to prostaglandins. There are also animal studies indicating that ROCK inhibitors may improve blood flow to the optic nerve, increase ganglion cell survival, and reduce bleb scarring in glaucoma surgery. Given the multiple beneficial effects for glaucoma patients, ROCK inhibitors are certainly a highly anticipated emerging treatment option for glaucoma.